Sayyid Sabiq's thoughts on Thalak in the book Fiqh Assunnah - Joseph Antoni; Akmal Abdul Munir (Priviet Social Sciences Journal, 2026)
This study aims to analyze a place of thought from Sayyid Sabiq's shop about thalak as contained in a poplar work of Fiqh As-Sunnah. This study focuses on his views on the facts, conditions, forms, and wisdom of a thalak from the perspective of Islamic fiqh. Thus, this larya imiah uses a qualitative approach, namely, library research on primary sources of Fiqh As-Sunnah by Sayyid Sabiq, as well as secondary sources from classical fiqh books and contemporary Islamic law literature. The results of the study show that Sayyid Sabiq understood thalak not as a means to oppress women, but as the last way out (the shari'i emergency way) when the goal of marriage can no longer be achieved. He emphasized that thalak must be pursued with full responsibility, based on the principle of justice. In his view, the law of thalak is mubah, but it becomes makruh if it is done without a good reason. Sayyid Sabiq's thinking shows a strong relevance to the context of Islamic family law in moderation, as it provides a balance between the right of men and women to impose thalak and women's right to self-justice. This research contributes to the development of more rational Islamic family law, to the benefits of sharia.